MENGGUNAKAN SPEECH FUNCTION DI KELAS BERBAHASA INGGRIS - Wiyanto, Muhammad Saibani (English Education:Journal of English Teaching and Research, 2020)
This study deals with the utterance of English teachers of SMP A. Wahid Hasyim Tebuireng. It is aimed to know the type of speech function used by English teacher in the classroom, and to find out how speech functions are applied by English teacher in the classroom. The researcher applies qualitative design and content analysis design as the approach based on Ary et al (2010). The subject of this research was English teacher in SMP A. Wahid Hasyim Tebuireng. The source of the data is subject in where the data obtained, while the data is the utterances used by English teacher. The researcher used observation and audiovisual material of collecting data. The data of transcription are classified into six basic types of speech function. There are expressive, directive, referential, metalinguistic, poetic and phatic. The researcher observed an English teacher. From the teacher who observed, the researcher found different total utterances from each meeting. The total utterance is 41 utterances which classified into five types of speech function. How speech functions are applied by English teacher in the classroom is when the teacher interaction with her students.